Presence of a neuropathic pain component in patients with chronic pain after gunshot wounds - V.R. Horoshko; Yu. L. Kuchyn (Клінічна та профілактична медицина, 2023)
In patients with gunshot wounds, chronic pain is observed in 70% of cases. One of the factors that influence such a high frequency of pain chronicity is the number of localizations of injured anatomical parts of the body – in patients with injuries in 1 or 2 anatomical parts of the body, the frequency of chronicity is 69.7%, and in patients with injuries in 3 – 71.2% of cases. Also, the presence of a neuropathic component of pain in this category of patients and its possible impact on such a high frequency of chronicity remains unexplored.